NILAI-NILAI KEARIFAN EKOLOGIS MASYARAKAT ADAT KRUI SEBAGAI ALTERNATIF SUMBER BELAJAR IPS SD-SMP DI PESISIR BARAT LAMPUNG - Novia Fitri Istiawati (Universitas Islam Balitar, 2016)
This study aims to (1) see history and characteristics of local indigeneous ecologies of Kui traditonal community, (2) obtain values of local genius on ecology that is possible to integrate into social sciences subject, and (3) model of local indigeneous ecologies of Krui tradional community as alternatives of learning sources of cocial science subject. The study used ethnography applied in qualitatuve approach. The study revealed: (1) Krui traditional community has their own local indigeneous ecologies to utilize and sustain forest, (2) values of local indigenius ecologies include: sustaining environment, cooperation work, adherence to the law, simple and self-reliance, democracy, work hard, sustainable and honest; (3) values of local genius in ecolocy are applicable to integrate in the learning sources of social sciences of grade: IV, V, and VI of SD levels and garde VII and VIII of SMP levels.